Ethnomedicinal and Ethnopharmacology Value of Plants Used by Kenyah in Borneo: A Review - Kho, Swen Jack; Juna, Liau; Mohd Razip, Asaruddin; Showkat, Ahmad Bhawani (UNIMAS Publisher, 2025)
Numerous societies across the globe rely on medicinal plants as a primary therapeutic resource. These plants have a long history of use in traditional medicine among several indigenous communities in Borneo. Among these communities is the Kenyah, who have an extensive heritage of relying on plants for medicinal purposes. The purpose of this review is to examine and compile the ethnomedicinal utilisation of plants by the Kenyah people of Borneo. This review included and documented different plants used by the locals of Borneo particularly Kenyah of Kalimantan and Sarawak for various medicinal purposes. The plants are grouped into family name, scientific name, and local name. Tabulation of each plant's specific treatment remedy after the method of administration, which may involve crushing and drinking an infusion, applying a poultice externally, grinding the plant into a paste, or inhaling smoke were done. The documentation identified 61 plant families, and several traditional treatment groups. Selected plants are scrutinized for their existing data on traditional usage to determine further potential and research gaps for research of the plants relating with the Kenyah ethnomedicinal knowledge.